Serum IL-1RA Levels Predict IVF Outcome in Caucasian But Not African American Women [10B]. (May 2018) - Elder, Simone; Irani, Mohamad; Witkin, Steven S.; Spandorfer, Steven D.
Abstract : INTRODUCTION: A growing body of evidence has shown that some cytokines are implicated in embryo development and implantation. Previous studies have suggested that serum levels of interleukin-1β (IL-1β) and interleukin-1 receptor antagonist (IL-1RA) can predict IVF outcome. However, the majority of included patients were Caucasian (C). Therefore, we investigated whether IL-1β and IL-1RA are expressed differently and have different predictive values of IVF outcome between C and African American (AA) women. METHODS: A retrospective study including 129 C and 88 AA women undergoing fresh IVF cycles. Serum levels of IL-1β and IL-1RA on cycle day (CD) 2 (before starting ovarian stimulation) and CD28 (14 days after oocyte retrieval) were compared between those who did or did not become pregnant. Values were expressed as mean±SEM. t -test was used as appropriate. RESULTS: C women had higher serum IL-1β levels compared to AA patients on CD2 (23.3±8.1 vs. 15.3±12.9 pg/mL, P=0.02). The IL-1RA level on CD 28 in C women, who achieved a pregnancy was higher as compared to those who did not become pregnant (488.2±83.9 vs. 183.4±45.3 pg/mL, P=0.02). In contrast, IL-1RA levels on CD28 were comparable between AA women who did or did not become pregnant (343.8±83.9 vs. 627.4±404.9, P=0.5). CONCLUSION: C women have different levels of IL-1 family cytokines as compared to AA women. Serum IL-1RA levels can predict IVF outcome in C but not in AA women. We are currently conducting a prospective study to examine the racial differences in additional cytokines among women undergoing IVF.